PENGENDALIAN PEMANFAATAN TAMAN KOTA - Bambang Rudiansah (FISIP Universitas Langlangbuana, 2019)
This research is motivated by the non-fulfillment of the green open space standards of Bandung City Park in Sumur District, Bandung City. In the analysis of the control aspects, researchers formulated the problem as follows: (1) How to control green open spaces (RTH) of city parks in Sumur District, Bandung. (2) Supporting and inhibiting factors in meeting green park open space (RTH) standards in city parks in Sumur District, Bandung. (3) What efforts are made to meet the green open space (RTH) standard of city parks in Sumur District, Bandung. The research method used in this study is a descriptive research method with a qualitative approach. Data obtained through participant observation, in-depth interviews, and documentation. The results of this study indicate that the control of green open spaces in city parks in the Sumur Bandung District area of ​​Bandung City which is based on Regional Regulation No. 18 concerning the Regional Spatial Plan (RTRW) of Bandung City has not met the spatial utilization standards in accordance with the Regional Spatial Plan (RTRW), There are several inhibiting factors. To overcome barriers to utilization, various efforts have been made in the participation of the community or park users, among others: Appeals regarding environmental preservation, especially city parks, creating environmental communities. But still there is a lack of participation or lack of awareness from the community and park users. Increase public understanding of green open spaces, especially city parks. The existence of periodic supervision and implementation of green open space, the community should be involved at least involved people such as community leaders, so as to foster a greater sense of responsibility.